ADVANTAGES OF INVOLVING STUDENTS IN OFF-CURRICLES CREATIVE CLUBS - Nutfullayev Muxtor Ne’matovich (Web of Journals Publishing, 2024)
The purpose of this article is to explore the benefits of engaging students in creative clubs outside of the learning process. The article proves that students can develop new skills, develop critical thinking, and enhance their ability to express themselves not only through theoretical knowledge acquired during the lesson, but also through creative activity.
Keywords: circle, training, skill, design, artistic ability, aesthetics.